Creative Re-subjectivations: Becoming-Animal in the Films of Matteo Garrone and David Cronenberg - Sticchi, Francesco; Angeli, Silvia (Quaderni d'Italianistica)

(untitled) (Iter Press, 2025)
This essay considers the posthuman and ecological tensions pervading the respective filmographies of Matteo Garrone and David Cronenberg. Taking our cue from Gilles Deleuze and Félix Guattari’s concept of becoming-animal, we investigate the recurring motifs and philosophical concerns that emerge from particular filmic ecologies and the characters inhabiting them. By displaying figures that appear dominated by fluxes of desires and passions they neither control nor manage through self-reflection and detached awareness, Garrone’s and Cronenberg’s cinemas challenge any image of rationality ostensibly embedded in the human. The encounters with the material and technological world that surround the individuality of characters do not necessarily define affirmative processes of becoming, but they do help us understand the dynamic nature of subjectivity and the always surprising possibilities for de-subjectivation and creative re-subjectivation. Here we focus on four works: Garrone’s The Embalmer (2002) and Dogman (2018), and Cronenberg’s The Fly (1986) and Crash (1996).